The Text Structure of The Simalungunese Turiturian Art, Culture, Media, and Education - Ibrahim Syah H.M. Simbolon; Robert Sibarani; Eddy Setia; Amrin Saragih; Nurlela; T. Thyrhaya Zein (East Asian Journal of Multidisciplinary Research, 2022)
The research formulates and explains the structure, the value, and the norms of disclosing local wisdom in the structure text of TS (Simalungunese 'turiturian' folklore). The narrative text identifies words, paragraphs, phrases, based on the structural text as Orientation ^ Sequence of event (crisis and climax) ^ Resolution ^closure. It is analyzed by using LSF (Functional Systemic Linguistics) text structure which is realized into narrative text structure by using FI (Ideational Function). Oral text sees the establishment of text, co-text, and context in the study of local wisdom. The research design uses interactive modal with descriptive qualitative, using documentary study paradigm in the content analysis in four TS Text. The type of narrative text finds the form of irregular structure texts is identified by the symbol of brackets ([]) which can occur in every stage in the TS text: (Abstract) ^ Orientation ^ ([Evaluation]) ^ Complication ^ Resolution ^ (Code). Ideational function indicates more dominant data in each stage of the proportion of material process of 85.7%, circumstance location of 80% so that para-tactical multiple logic us 1x2 60%. This proportional data indicates that there are 16 verbal words in material data, circumstance data indicate data location which modify 12 location data, logic meaning data indicate that the data taken from verbal data are identified with conjunctions such as that, then, (and) after that, for that, etc. Value and norms contained in the TS text which dominate every text are the values of hard work, togetherness, and discipline. The local wisdom is found in the value and norms of the people's custom described as the forms of behavior and custom in the TS Text. Therefore, this discussion is a unit which also discusses the structure and values of the local cultural wisdom.